ANALISIS TINGKAT KEMATANGAN INDUSTRI KOMPONEN OTOMOTIF DI INDONESIA - Franka Hendra (University of Muhammadiyah Jakarta, 2017)
The main purpose of this paper is to obtain a portrait of the level of maturity (maturity level) automotive component industry in Indonesia. With the completion of the level of maturity of industry ritating component parts can be recommended treatment is needed for each industry based on the level. In accordance with the objectives to be achieved, the scope of this activity is only focused on a rotating component wheel vehicle part 4 (four). The conceptual development stages of maturity level models (maturity level) automotive components industry, which are as follows: Desk review, collection and development of data using secondary data is required, Collection and selection of manufacturing industry maturity model framework, Preparation checklist or questionnaire, Implementation of the framework was elected in selected automotive components industry and Do the processing, calculation and analysis of data with the approach of maturity models. The result of this paper is Indonesia's automotive component industry has the potential to be developed and reliable, and can be one of the competitive component suppliers in vehicle production in ASEAN. However, existing capabilities must be improved.